The relationship of body mass index, leg muscle strength to maximal oxygen volume optimization in students - Wahyu Hananingsih; Khaerani Saputri Imran; Sylvana Yaka Saputra; Anisa Komala Dewi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Physical condition, including body mass index (BMI) and leg muscle strength, is a key factor influencing athletic performance, particularly in volleyball. This study aimed to examine the relationship between BMI and leg muscle strength with maximal oxygen uptake (VO₂ max) in volleyball athletes. A non-experimental quantitative correlational design was applied with a total sample of 30 university volleyball players. Data were collected using standardized measurements of BMI, leg muscle strength, and the multistage fitness test (MFT) to estimate VO₂ max. Normality and linearity tests were conducted before correlation analysis. Results showed an average BMI of 21.69, leg muscle strength of 70.27, and VO₂ max of 32.16. Multiple correlation analysis indicated a significant relationship between BMI and leg muscle strength with VO₂ max (Sig. F change = 0.003 < 0.05, R = 0.597, R² = 0.356). These findings suggest that optimal BMI and strong lower limb muscles jointly support aerobic capacity in volleyball athletes, providing evidence for targeted physical training programs that enhance both fitness and performance.